The defeat of the 6th and 12th Soviet armies in the summer of 1941 as repoted by Ukrainian-language newspapers during the Nazi occupation - Grinchenko , Victor (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Aim of the study. Highlight and analyze various information related to the defeat of the 6th and 12th Soviet armies in the summer of 1941 in the materials of Ukrainian-language newspapers published in 1941–1944 in the occupied territories of Ukraine and beyond. Research methodology. The principles of historicism, objectivity, comprehensiveness and integrity of the study of the source are applied. The methods used include descriptive, historical-comparative, historical-critical methods, historiographical analysis and synthesis. Scientific novelty. The materials presented in this publication can serve as a certain addition to already existing scientific research on the coverage of the defensive battles of the 6th and 12th Soviet armies in the summer of 1941 and their interpretation by one of the opposing sides in the German-Soviet war. Conclusions. It was established that the relevant publications of Ukrainian-language newspapers presented information on the quantitative indicators of losses of Soviet troops in manpower and equipment as a result of their defeat near Uman in the summer of 1941; assessments of the importance of this battle for the offensive actions of the German army; comparison of the losses of the WPRA in this battle among other military campaigns of 1941; judgments about the reasons for the defeats of the Soviet army, including at Uman; mentions of individual facts, local episodes of military actions during this battle; information about Soviet generals captured near Uman. These newspaper materials, despite their censorship and bias, are of scientific interest and can be used in conjunction with other sources to cover various aspects of the tragedy of the 6th and 12th armies in the summer of 1941, which will enable assessing the level of objectivity of the information they presenteded.